THEY’RE HEALTHY, THEY’RE SUSTAINABLE ALTERNATIVE FOOD SOURCES. WHY DON’T MALAYSIANS AND INDONESIANS EAT MORE BUGS? - Teng, Phuah Kit; Cokki, Cokki; Waei, Ow Mun; Wai, Khoong Tai (International Journal of Application on Economics and Business, 2025)
In recent years, the consumption of healthy foods, particularly organic options, has emerged as a key factor in driving sustainable transformation. However, the rising global population, increasing incomes, and urbanization have intensified concerns over food security due to the depletion of natural resources. To address these challenges, governments and businesses have introduced strategies such as adopting innovative, efficient, and cost-effective technologies to enhance agricultural productivity. Despite these efforts, food insecurity remains a significant issue for low-income households in developing countries, including Malaysia and Indonesia. This study aims to explore the influence of trust, food neophobia, perceived benefits, perceived risks, and perceived naturalness on consumer acceptance of edible insects in Malaysia and Indonesia. Data was collected through purposive sampling from 388 respondents, comprising 288 Malaysians and 100 Indonesians, using a structured questionnaire. Hierarchical multiple regression analysis was conducted using SPSS to test the proposed relationships. The findings reveal that trust (in the individual endorsing the product), perceived benefits, perceived naturalness, and food neophobia significantly affect consumer acceptance of edible insects. Moreover, nationality moderated the relationship between perceived risks and perceived benefits, with these factors having a stronger impact on Malaysian and Indonesian consumers. This study contributes to the understanding of consumer behavior in the emerging edible insect market and provides valuable insights for businesses and professionals to develop more effective marketing strategies aimed at increasing demand for edible insect-based food products.